Inter-domain routing security mechanism for crossing autonomous system alliance - Ling-jing KONG; Hua-xin ZENG; Jun DOU; Yao LI (Tongxin xuebao)
Through studying and analyzing SE-BGP (security enhanced BGP),it was found that it couldn’t validate the cross-alliance AS (autonomous system) and defense the self-launched active attack.To solve the security problems,two-layer cross-alliance hierarchical structure CAHS (cross-alliance hierarchical structure) was designed.Based on CAHS,using the idea of passport visa and the features of AdHASH (additive hash),a cross-alliance BGP security mechanism SCA-BGP (secure crossing alliance for BGP) was proposed.The mechanism has higher security,which is able to effectively validate the identities and behavior authorization of the cross-alliance AS as well as the message carried by them.The experiment results show that SCA-BGP can effectively reduce the certificate scale and extra time overhead to get better scalability and convergence performance.